CITRAAN DALAM KUMPULAN PUISI AYAT-AYAT API KARYA SAPARDI DJOKO DAMONO - M. Aris M. Aris; Erlina Zahar; Sujoko Sujoko (Universitas Batanghari, 2019)
The purpose of this research is to describe the imagery in the poetry collection Ayat-ayat Api by Sapardi Djoko Damono. This research is qualitative descriptive. The main data is taken from the written excerpt which consists of imagery in the poetry collection Ayat-ayat Api by Sapardi Djoko Damono. The data is collected by using library technique which focused on imagery analysis in the poetry collection Ayat-ayat Api by Sapardi Djoko Damono. The data is analyzed by using analysis and descriptive technique. Based on the result of the analysis, it can be concluded that there are sight imagery, hearing imagery, movement imagery in 15 poetry collection Ayat-ayat Api by Sapardi Djoko Damono. So it can be said that there are, 1) sight imagery consists of 10 expressions. 2) Hearing imagery consists of 10 expressions. 3) Movement imagery consists of 11 expressions. Thus, all of the expressions from that three imagery are 31 expressions from 15 poetry collection in Ayat-ayat Api by Sapardi Djoko Damono. Keywords: Analysis, Imagery, Poetry Collection